2015
DOI: 10.1186/s12933-015-0223-2
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inflammation and nitric oxide-mediated alterations in cardiovascular function are major determinants of endotoxin-induced insulin resistance

Abstract: BackgroundEndotoxin (i.e. LPS) administration induces a robust inflammatory response with accompanying cardiovascular dysfunction and insulin resistance. Overabundance of nitric oxide (NO) contributes to the vascular dysfunction. However, inflammation itself also induces insulin resistance in skeletal muscle. We sought to investigate whether the cardiovascular dysfunction induced by increased NO availability without inflammatory stress can promote insulin resistance. Additionally, we examined the role of induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 62 publications
(77 reference statements)
3
23
0
Order By: Relevance
“…However, we found that NO had no effect on either TIE or accumulation of 2[ 14 C]DGP in the gastrocnemius. This finding is largely consistent with those of previous studies, which showed that SNP infusion either does not alter insulin-stimulated glucose disposal (50) or slightly reduces it (34). One limitation of our study is that, despite infusing a high dose of SNP, which was previously shown to have major cardiovascular and metabolic effects (34), BP was lowered by only ;10 mmHg, and the 40% increase in VASP activation (i.e., NO signaling) was not significant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, we found that NO had no effect on either TIE or accumulation of 2[ 14 C]DGP in the gastrocnemius. This finding is largely consistent with those of previous studies, which showed that SNP infusion either does not alter insulin-stimulated glucose disposal (50) or slightly reduces it (34). One limitation of our study is that, despite infusing a high dose of SNP, which was previously shown to have major cardiovascular and metabolic effects (34), BP was lowered by only ;10 mmHg, and the 40% increase in VASP activation (i.e., NO signaling) was not significant.…”
Section: Discussionsupporting
confidence: 93%
“…6A). This dose was chosen on the basis of a previous study that showed that a 37 mg/kg/min infusion lowered BP within 15 min (34). We increased this dose to ensure that SNP would be effective in anesthetized mice.…”
Section: Treatment Protocolsmentioning
confidence: 99%
“…It did, however, attenuate the LPS-induced impairment in cardiac output and induced adaptations that sustained anaerobic glycolysis. Our previous findings suggested that alterations in muscle glucose delivery play a critical role in insulin resistance resulting from LPS (5, 19). These results suggest that the protective effect of GLUT4 overexpression is not due to maintenance of transport capacity but in part due to the maintenance of cardiac function in response to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments showed that ALP upregulation was demonstrated in the vascular wall of diabetic rat and mouse models of vascular calci cation [23]. (2) Higher serum ALP was associated with increased risk of endothelial dysfunction, a process related to insulin resistance, an initial process to diabetes [24]. This was explained that ALP could reduce nitric oxide (NO) bioavailability by inhibiting tyrosine kinase activity into endothelial cells [25], leading to the consequent impairment of endothelial NO synthase function [26].…”
Section: Discussionmentioning
confidence: 99%